A study of police womens' career advancement in Ibu Pejabat Kontinjen Sarawak - Ma, Audrey Wen Fong (Universiti Malaysia Sarawak (UNIMAS), 2015)
This study aims at identifying the factors that contribute to police womens' career advancement in Ibu Pejabat Kontinjen Sarawak. This study followed a quantitative approach where questionnaires in the form of five Likert Scale were used to collect data from respondents. The study has 83 respondents of sample size. The Statistical Package for Social Science (SPSS) version 20.0 namely descriptive statistic is used to analyze the data collected from the respondents. The relationship between equality of treatment, work pressure, flexible working procedures, job satisfaction and police women's career advancement was examined using Pearson Correlation Coefficient analysis. The result shows all of independent variables have a significant relationship with police womens' career advancement. The multiple regression result obtained indicated that equality of treatment is not dominant factor for police womens' career advancement. The recommendations for organization, human resource practitioners, police women and future researchers were also further discussed.